Bathymetry and Agricultural Crop Studies From ICESat‐2: The Density‐Dimension Algorithm - Xiaomei Lu; Yongxiang Hu; Ali Omar; Charles R. Trepte (Earth and Space Science, 2025)
Abstract The Density‐Dimension Algorithm (DDA) was originally developed to retrieve land surface, vegetation canopy, and sea ice freeboard heights from the photon clouds measured by the multi‐beamed micropulse lidar flying aboard NASA's Ice, Cloud, and land Elevation Satellite‐2 (ICESat‐2) mission. The DDA employs weight functions to calculate a density field, thereby introducing an additional dimension to the photon clouds. Then, the density field is analyzed using local peak and threshold methods to facilitate the separation of feature signal photons from nearby noise photons. In this work we extend the DDA to water bathymetry (DDA‐bathymetry) and agricultural crop (DDA‐crop) studies. Our results demonstrate that the technique effectively identifies bathymetric and crop photons across various background conditions, including clear water, turbid water with increased suspended particles, nighttime observations with reduced background noise, and daytime observations with solar background noise.